Seismicity and Pn Velocity Structure of Central West Antarctica. (19th February 2021) - Lucas, Erica M.; Nyblade, Andrew A.; Lloyd, Andrew J.; Aster, Richard C.; Wiens, Douglas A.; O'Donnell, John Paul; Stuart, Graham W.; Wilson, Terry J.; Dalziel, Ian W. D.; Winberry, J. Paul; Huerta, Audrey D.
Abstract: We have located 117 previously undetected seismic events mainly occurring between 2015 and 2017 that originated from glacial, tectonic, and volcanic processes in central West Antarctica using data recorded on Polar Earth Observing Network (POLENET/ANET) and UK Antarctic Network (UKANET) seismic stations. The seismic events, with local magnitudes ( M L ) ranging from 1.1 to 3.5, are predominantly clustered in four geographic regions; the Ellsworth Mountains, Thwaites Glacier, Pine Island Glacier, and Mount Takahe. Eighteen of the events are in the Ellsworth Mountains and can be attributed to a mixture of glacial and tectonic processes. The largest event noted in this study was a mid‐crustal (∼19 km focal depth; M L 3.5) normal mechanism earthquake beneath Thwaites Glacier. We also located 91 glacial events near the grounding zones of Thwaites Glacier and Pine Island Glacier that are predominantly associated with time periods of significant calving activity. Eight events, likely arising from volcano‐tectonic processes, occurred beneath Mount Takahe. Using Pn travel times from the seismic events, we find laterally variable uppermost mantle structure in central West Antarctica. On average, the Ellsworth Mountains are underlain by a faster mantle lid ( V Pn  = ∼8.4 km/s) compared to the Amundsen Sea Embayment region ( V Pn  = ∼8.1 km/s). Within the Amundsen Sea Embayment itself, we find mantle lid velocities ranging from ∼8.05 to 8.18 km/s. Laterally heterogeneous uppermost mantle structure, indicative of variable thermal and rheological structure, likely influences both geothermal heat flux and glacial isostatic adjustment spatial patterns and rates within central West Antarctica. Plain Language Summary: In this study, we have identified and located 117 seismic events in central West Antarctica. The seismic events originate from both solid‐Earth and glacial processes. While the seismic events originating from solid‐Earth processes are associated with tectonic and volcano‐tectonic activity in central West Antarctica, the seismic events arising from glacial processes are predominantly associated with time periods of significant calving activity at Thwaites Glacier and Pine Island Glacier. Using select P‐waves produced by seismic events located in this study, we investigate the uppermost portion of the mantle beneath central West Antarctica and find that the temperature of the uppermost mantle likely varies by at least 160 K across central West Antarctica. Variable uppermost mantle temperatures have numerous implications for the dynamics and evolution of the West Antarctic Ice Sheet. Key Points: Located 117 previously undetected seismic events of glacial, tectonic, and volcano‐tectonic origin Laterally variable Pn velocity structure across central West Antarctica